EDUCATORS' STRATEGIES IN IMPLEMENTING TOLERANCE VALUES TO ANTICIPATE NEGATIVE BEHAVIOR AT THE ELEMENTARY SCHOOL LEVEL - annisya anggreiny; yurma vadelta; neng sarah aprilia; daffa diyah ulhaq (Journal of Pedagogical Content Knowledge, 2025)
This research aims to analyze the phenomenon of bullying in elementary school (SD) students, including prevalence, causal factors, impacts, and prevention efforts that can be carried out by schools. Bullying in elementary school age children often occurs in physical, verbal and social forms, with a significant impact on the victim's psychology and academic achievement. Factors that encourage bullying include lack of supervision from parents and teachers, a family environment that is not conducive, and negative influences from peers. The impact of bullying on victims is very diverse, ranging from decreased self-confidence, anxiety, to long-term mental disorders. This research emphasizes the important role of schools in implementing comprehensive anti-bullying programs, educating children about the importance of empathy, and involving parents in preventing and handling bullying. In conclusion, collaboration between schools, families and communities is very necessary to create a safe environment and support the overall development of students.